Novel balanced single/dual‐band bandpass filters based on a circular patch resonator - Qiao Zhang; Chang Chen; Weidong Chen; Jun Ding; Hualiang Zhang (IET Microwaves, Antennas & Propagation, 2021)
Abstract A new strategy for designing single‐band and dual‐band balanced bandpass filters (BPFs) based on a circular patch resonator is proposed in this study. By altering the output balanced ports of the balanced BPFs to inhibit or transport the TM31 mode of the circular patch resonator under the differential‐mode (DM) excitation, a single‐band or dual‐band balanced BPF can be realized. As the odd modes could be restrained under the common‐mode (CM) excitation, the balanced BPFs could feature high CM suppression in the DM passbands. Meanwhile, several perturbing tactics are introduced to improve the performance of the balanced BPFs. Specifically, perturbation vias are presented to disturb the electric field distribution to enhance the CM suppression in the DM passbands, and slots are applied on the circular patch resonators to perturb the current distribution to amend the second DM passband of the dual‐band balanced BPF. The proposed single‐band and dual‐band balanced BPFs are fabricated and characterized. Good agreement can be achieved between the simulated and measured results of the fabricated balanced BPFs, which validates the feasibility of the proposed design method.